Lightweight high-strength high-entropy Al alloy block material as well as preparation method and application thereof

By designing high-entropy Al alloys and using high temperature and high pressure treatment, lightweight high-strength high-entropy Al alloy materials with face-centered cubic solid solution phases are prepared, which solves the problem of limited mechanical properties of existing aluminum alloys, achieves the balance of high specific strength and low density, and improves stability and processing performance.

CN119571178AActive Publication Date: 2025-03-07UNIV OF SCI & TECH BEIJING
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411841928.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-07
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

While the existing aluminum alloys pursue high specific strength and low density, their mechanical properties are limited and it is difficult to achieve high entropy effect, resulting in poor stability under extreme conditions.

Method used

By designing a high-entropy Al alloy, using the atomic percentage expression of AlaMgbLicZndMe, combined with high temperature and high pressure treatment, a lightweight, high-strength, high-entropy Al alloy material with a face-centered cubic solid solution phase was prepared.

Benefits of technology

It achieves a balance of high specific strength and low density, improves the compressive strength and compressive plasticity of the alloy, and improves the stability and processing performance under extreme conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571178A_ABST
    Figure CN119571178A_ABST
Patent Text Reader

Abstract

The invention discloses a lightweight high-strength high-entropy Al alloy block material and a preparation method and application thereof. The atomic percentage expression of the high-entropy Al alloy block material is AlaMgbLicZnd, and the atomic percentage content of each component is as follows: 40 < = a < = 80 at%, 15 < = b < = 50 at%, 0 < c < = 20 at%, 0 < d < = 20 at%, and a + b + c + d = 100%. Alloy components are obtained through design, then the structure of the AlMgLiZn system light high-entropy alloy is regulated and controlled through different high-temperature and high-pressure treatments, various brittle intermetallic compound phases in an initial alloy are converted into face-centered cubic solid solutions, the grain boundary binding force is enhanced, and generation of intercrystalline cracks in the early deformation stage is restrained. And finally, the light-weight high-strength high-entropy Al alloy block material with the density being 2.4-2.86 g / cm < 3 >, the compressive strength being 600-980 MPa and the compression plasticity being 2.5%-35% at the room temperature is obtained, and the alloy can be used for preparing parts and structural parts for air transportation equipment and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of functional materials, and in particular relates to a lightweight, high-strength, high-entropy Al alloy block material, a preparation method and an application thereof. Background Art

[0002] Lightweight alloys have the characteristics of low density, high specific strength, and high specific modulus, so they have been widely used in aerospace, automotive, electronics, military and other fields. Due to their low density, lightweight alloys can significantly reduce the weight of structural components, improve fuel efficiency and reduce energy consumption, especially in the aerospace and automotive industries, which is crucial for reducing emissions and improving performance. With the continuous advancement of science and technology, the research and development and application prospects of lightweight alloys are broad. For example, aluminum alloys account for a very large proportion of the application in the aerospace field, which can greatly reduce energy consumption, save energy and reduce emissions. However, since its main component is a single element, it is limited in the pursuit of more comprehensive physical, chemical and mechanical properties. Generally, the aluminum content in aluminum alloys exceeds 85at%, and more light elements need to be introduced to further reduce the density. However, exceeding the solubility limit of these elements in aluminum may cause the alloy to be mainly composed of intermetallic compounds (IMCs) and lack a ductile face-centered cubic matrix, resulting in deterioration of mechanical properties. In addition, strength generally decreases with decreasing density, which makes it very challenging to achieve high specific strength in aluminum alloys.

[0003] "High entropy" is a new material design theory that has emerged in recent years. High entropy alloys are alloy materials mixed with multiple principal components. Due to the unique structural characteristics such as high mixing entropy, lattice distortion, chemical short order, slow diffusion, etc. brought about by the "high entropy effect", it has unique performance characteristics. Compared with traditional alloys, high entropy alloys have higher solid solution stability, excellent mechanical properties (such as high strength and high hardness), excellent corrosion resistance and oxidation resistance. Due to its multi-component design concept, the physical and chemical properties of high entropy alloys often show excellent performance of non-traditional alloys, and can operate stably for a long time under extreme conditions (such as high temperature, high pressure or corrosive environment).

[0004] By using the high entropy concept to dissolve more light elements in Al alloys and designing high entropy Al alloys, it is expected that new aluminum alloys with excellent comprehensive mechanical properties will be developed. At present, due to the significant difference in atomic radius and electronegativity between aluminum and other light elements, the system has high mixing enthalpy and low excess entropy. In this case, chemically ordered IMCs are more likely to form. This leads to the deterioration of the mechanical properties of the alloy. Therefore, it is urgent to develop high-performance high-entropy Al alloy materials with face-centered cubic solid solution as the matrix phase and their preparation methods. Summary of the invention

[0005] The invention discloses a high entropy Al alloy material with excellent comprehensive mechanical properties and a preparation method thereof, so as to solve any of the above and other potential problems of the prior art.

[0006] In order to solve the above technical problems, the technical solution of the present invention is: a lightweight, high-strength, high-entropy Al alloy bulk material, the atomic percentage expression of the high-entropy Al alloy bulk material is Al a Mg b Li c Zn d The atomic percentage of each component is: 40≤a≤80at%, 15≤b≤50at%, 0<c≤20at%, 0<d≤20at%, and a+b+c+d=100at%.

[0007] Furthermore, the high entropy Al alloy bulk material further comprises M e , M is at least one of Cu, Y, La or Ce, and 0≤e≤20at%.

[0008] Furthermore, the lightweight, high-strength, high-entropy Al alloy bulk material has a face-centered cubic solid solution structure composed of multiple principal metal elements.

[0009] Further, when M is Cu, a=70at%, b=15at%, c=5at%, d=5at%, e=5at%, the atomic percentage expression of the high entropy Al alloy bulk material is Al 70 Mg 15 Li5Zn5Cu5, density 2.7 g / cm 3 , at room temperature, the compressive strength is 770MPa and the compression plasticity is 31%.

[0010] Further, when a=40.0at%, b=40.0at%, c=10.0at%, d=10.0at%, the atomic percentage expression of the high entropy Al alloy bulk material is Al 40 Mg 40 Li 10 Zn 10 , density is 2.54 g / cm 3 , at room temperature, the compressive strength is 880MPa and the compression plasticity is 2.5%.

[0011] Another object of the present invention is to provide a method for preparing the above-mentioned high entropy Al alloy material, the preparation method specifically comprising the following steps:

[0012] S1) Weigh each raw material according to the designed ratio. The purity of the raw material exceeds 99.9%. Remove the surface oxide layer and ultrasonically clean it in ethanol or acetone; (raw materials include Al, Mg, Li, Zn, Cu, Y, La, Ce)

[0013] S2) melting the raw materials processed in S1) in a vacuum induction melting furnace to obtain alloy ingots;

[0014] S3) Using a two-stage large press, the alloy ingot obtained in S2) is subjected to high temperature and high pressure treatment to obtain a lightweight, high-strength, high-entropy Al alloy block material with a face-centered cubic solid solution phase.

[0015] Furthermore, the specific process parameters in S2) are: the smelting atmosphere is high-purity argon; and the smelting temperature is 700-900°C.

[0016] Furthermore, in said S3), the high pressure range is 10-15 GPa, the high temperature range is 1000-1500 K, and the holding time is 5-10 min.

[0017] Furthermore, the density of the lightweight, high-strength, high-entropy Al alloy bulk material prepared by the preparation method is 2.4-2.86 g / cm 3 At room temperature, the compressive strength is 600-980MPa and the compression plasticity is 2.5%-35%.

[0018] The above-mentioned lightweight, high-strength, high-entropy Al alloy block material is used in the preparation of parts and structural parts of aviation transportation equipment. Furthermore, the raw materials used in the weighing are Al, Mg, Li, Zn, Cu, Y, La, and Ce with a purity exceeding 99.9%.

[0019] Furthermore, the high pressure range is 10-15 GPa, the high temperature range is 1000-1500 K, and the insulation time is 5-10 min.

[0020] A lightweight, high-strength, high-entropy Al alloy bulk material is used in the preparation of components and structural parts of aviation transportation equipment.

[0021] The mechanism of the present invention is: the present invention realizes high solid solubility of elements in Al through high temperature and high pressure, thereby synthesizing a supersaturated solid solution.

[0022] Among them, the density of Mg is only 1.74g / cm 3 The addition of Mg can significantly reduce the density of Al alloy, improve its strength, hardness, corrosion resistance, oxidation resistance and heat treatment performance, and improve the processing performance of aluminum alloy.

[0023] The density of Li is only 0.53 g / cm 3The addition of Li can significantly reduce the density of the alloy, which has a significant strength-to-weight ratio advantage and improves the strength, plasticity, and fatigue resistance of the alloy. In addition, the addition of Li reduces the thermal expansion coefficient of the alloy, making it less likely for the alloy to undergo a significant volume change when the temperature changes, and has high-precision applications.

[0024] The proper addition of Cu to Al can improve its high-temperature performance by enhancing the high-temperature strength of aluminum alloys. The addition of Y element to Al can play a role in grain refinement, which helps to improve the mechanical properties of the alloy, especially strength and toughness, and can also improve the stability of aluminum alloys at high temperatures. The Ce element can improve the casting and processing properties of aluminum alloys. In the casting process of Al alloys, Ce can help reduce casting defects (such as pores, shrinkage, etc.), make aluminum alloy castings denser, and improve processability. The addition of La element to Al can improve its high-temperature strength, oxidation resistance and corrosion resistance; improve the grain structure of Al alloys, increase the thermal stability of Al alloys, and also help to reduce the rupture of oxide films in the alloy and improve its performance in high-temperature environments.

[0025] The beneficial effects of the present invention are as follows: due to the adoption of the above technical solution, the present invention provides a new approach for developing more lightweight high-entropy alloys by combining the ratio of components with high temperature and high pressure to prepare a face-centered cubic solid solution phase AlMgLiZn-based lightweight high-entropy alloy;

[0026] The provided series of AlMgLiZn-based lightweight high-entropy alloys with face-centered cubic solid solution phase can be reasonably controlled in composition and high temperature and high pressure preparation conditions according to actual application requirements. Therefore, the alloy has a large composition application range and a wide range of preparation conditions.

[0027] The lightweight, high-strength, high-entropy Al alloy material prepared by the preparation method of the present invention has a density of 2.4-2.86 g / cm 3 At room temperature, the compressive strength is 600-980MPa and the compression plasticity is 2.5%-35%. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The cast Al 70 Mg 15 XRD pattern of Li5Zn5Cu5 alloy.

[0029] Figure 2 The cast Al 70 Mg 15 Room temperature compression curve of Li5Zn5Cu5 alloy.

[0030] Figure 3 The face-centered cubic structure Al 70 Mg 15XRD pattern of Li5Zn5Cu5 alloy.

[0031] Figure 4 The face-centered cubic structure Al 70 Mg 15 Room temperature compression curve of Li5Zn5Cu5 alloy.

[0032] Figure 5 The cast and face-centered cubic structure Al 70 Mg 15 SEM image of the microstructure of Li5Zn5Cu5 alloy.

[0033] Figure 6 The cast Al 40 Mg 40 Li 10 Zn 10 XRD patterns of the alloy.

[0034] Figure 7 The cast Al 40 Mg 40 Li 10 Zn 10 Room temperature compression curve of the alloy.

[0035] Figure 8 The face-centered cubic structure of the present invention is based on Al 40 Mg 40 Li 10 Zn 10 XRD patterns of the alloy.

[0036] Fig. 9 The face-centered cubic structure of the present invention is based on Al 40 Mg 40 Li 10 Zn 10 Room temperature compression curve of the alloy.

[0037] Fig.10 The Al2O3 of the present invention is a cast aluminum alloy having a face-centered cubic structure as the matrix. 40 Mg 40 Li 10 Zn 10 SEM image of the alloy's microstructure. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in combination with specific comparative examples and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0039] The present invention provides a lightweight, high-strength, high-entropy Al alloy bulk material, characterized in that the atomic percentage expression of the high-entropy alloy is Al a Mg b Li c Zn d M e , M=(Cu,Y,La,Ce)The atomic percentage of each component is: 40≤Al≤80at%, 15≤Mg≤50at%, 0<Li≤20at%, 0<Zn≤20at%, and a+b+c+d+e=100

[0040] The lightweight, high-strength, high-entropy Al alloy bulk material has a face-centered cubic solid solution phase structure composed of multiple principal metal elements.

[0041] The lightweight, high-strength, high-entropy Al alloy block material has low density, high strength and certain plasticity, and also has high specific fracture strength.

[0042] When M is Cu, a=70.0, b=15.0, c=5.0, d=5.0, e=5.0, the atomic percentage expression of the high entropy alloy is Al 70 Mg 15 The density of Li5Zn5Cu5 face-centered cubic solid solution material synthesized at high temperature and high pressure is 2.7 g / cm 3 , the maximum compressive strength at room temperature is 770MPa, and the plasticity reaches ~31%

[0043] When a=40.0, b=40.0, c=10.0, d=10.0, the atomic percentage expression of the high entropy alloy is Al 40 Mg 40 Li 10 Zn 10 The density of the face-centered cubic solid solution material synthesized under high temperature and high pressure is only 2.54 g / cm 3 , the maximum compressive strength at room temperature is 880MPa, and the plasticity is ~2.5%.

[0044] Another object of the present invention is to provide a method for preparing the above-mentioned lightweight, high-strength, high-entropy Al alloy material, the preparation method specifically comprising the following steps:

[0045] Step 1: Raw material preparation: Use pure elements as raw materials, remove the oxide layer and impurities of the metal elements, and ultrasonically clean them in ethanol or acetone;

[0046] Step 2: Weighing: Calculate the mass of each element according to the atomic ratio of each component and weigh and proportion them;

[0047] Step 3: Alloy smelting: using a vacuum induction melting furnace to melt the alloy to obtain an alloy ingot;

[0048] Step 4: High temperature and high pressure treatment: Use a two-stage large press to treat the obtained alloy ingot with high temperature and high pressure to obtain the lightweight, high-strength, high-entropy Al bulk alloy material of the face-centered cubic solid solution phase.

[0049] The raw materials used in the weighing are Al, Mg, Li, Zn, Cu, Y, La, and Ce with a purity exceeding 99.9%. Among them, Y is added using AlY master alloy.

[0050] The high pressure range is 10-15 GPa, the high temperature range is 1000-1500 K, and the insulation time is 5-10 min.

[0051] Example 1

[0052] Al 70 Mg 15 The preparation process of Li5Zn5Cu5 lightweight high entropy is as follows:

[0053] (1) Raw material preparation: Use pure elements as raw materials, remove the oxide layer and impurities of the metal elements, and ultrasonically clean them in ethanol or acetone; keep the Li element in a glove box for a long time, and use a blade to remove the surface oxide scale in the glove box when using it, and then cut out the sample without oxide scale, and wait for smelting after mixing the ingredients in the glove box;

[0054] (2) Weighing: The mass of each element is calculated according to the atomic ratio of each component, and the precise weighing and proportioning is performed using a precision electronic balance; this is used for alloy smelting, and the Li element is operated in a glove box;

[0055] (3) Alloy smelting: The ingot is prepared using a high vacuum induction melting furnace. Pure metals are placed in a crucible in turn and induction smelted in a high-purity argon environment. After the alloy is melted, it is poured into a mold to obtain a cast alloy ingot.

[0056] (4) High temperature and high pressure treatment: The obtained alloy ingot is subjected to a high temperature and high pressure treatment of 10 GPa / 1000 K using a two-stage large press. First, the alloy sample is assembled in the first and second stages. Next, the pressure is gradually increased to 10 GPa, and then heated to 1000 K, and the pressure and heat are gradually increased until the set value is reached. After reaching the set pressure and temperature, the high temperature and high pressure state is maintained for 5 minutes to ensure that the sample undergoes the required phase change. After the experiment, the temperature is lowered to room temperature, and then the pressure is gradually reduced to normal pressure to avoid damage to the sample or equipment due to drastic changes. Finally, the high temperature and high pressure sample is taken out for subsequent analysis.

[0057] The obtained cast and high temperature and high pressure alloy ingots are prepared into samples of certain specifications for testing and characterization.

[0058] The structure and performance of the cast and high temperature and high pressure alloys prepared by the above method are characterized as follows:

[0059] (5) Material phase characterization and mechanical properties testing:.

[0060] Figure 1 The Al 70 Mg 15 The XRD spectrum of the Li5Zn5Cu5 cast sample material shows that its main phase is face-centered cubic solid solution and various intermetallic compound phases, including Li3CuAl5. Figure 2 The Al 70 Mg 15 The room temperature compressive stress-strain diagram of the Li5Zn5Cu5 cast sample material shows that its maximum compressive strength at room temperature is 433MPa and the fracture strain is 19%; Figure 3 The Al 70 Mg 15 The XRD spectrum of the Li5Zn5Cu5 high temperature and high pressure sample material shows that it is composed of a single-phase face-centered cubic solid solution phase. It can be seen that after high temperature and high pressure treatment, the compound structure in the sample is transformed into a single-phase face-centered cubic solid solution phase structure. Figure 4 The Al 70 Mg 15 The room temperature compressive stress-strain diagram of the Li5Zn5Cu5 high temperature and high pressure sample material shows that its maximum compressive yield strength at room temperature is 770MPa and the fracture strain is 31%. It can be seen that the strength and plasticity of the synthesized single-phase face-centered cubic solid solution alloy are greatly improved. Figure 5 The Al 70 Mg 15 The SEM images of the organizational structure morphology of the Li5Zn5Cu5 cast and high-temperature and high-pressure sample materials clearly show the organizational morphology of at least two phase structures in the cast samples. After high-temperature and high-pressure treatment, a single-phase uniform face-centered cubic solid solution phase is obtained.

[0061] Example 2

[0062] Al 40 Mg 40 Li 10 Zn 10 The preparation process of lightweight high entropy is as follows:

[0063] (1) Raw material preparation: Use pure elements as raw materials, remove the oxide layer and impurities of the metal elements, and ultrasonically clean them in ethanol or acetone; keep the Li element in a glove box for a long time, and use a blade to remove the surface oxide scale in the glove box when using it, and then cut out the sample without oxide scale, and wait for smelting after mixing the ingredients in the glove box;

[0064] (2) Weighing: The mass of each element is calculated according to the atomic ratio of each component, and the precise weighing and proportioning is performed using a precision electronic balance; this is used for alloy smelting, and the Li element is operated in a glove box;

[0065] (3) Alloy smelting: The ingot is prepared using a high vacuum induction melting furnace. Pure metals are placed in a crucible in turn and induction smelted in a high-purity argon environment. After the alloy is melted, it is poured into a mold to obtain a cast alloy ingot.

[0066] (4) High temperature and high pressure treatment: The obtained alloy ingot is subjected to a high temperature and high pressure treatment of 10GPa / 1000K using a two-stage large press. First, the alloy sample is assembled in the first and second stages. Next, the pressure is gradually increased to 10GPa, and then heated to 1000 K, and the pressure and heat are gradually increased until the set value is reached. After reaching the set pressure and temperature, the high temperature and high pressure state is maintained for 8 minutes to ensure that the sample undergoes the required phase change. After the experiment, the temperature is lowered to room temperature, and then the pressure is gradually reduced to normal pressure to avoid damage to the sample or equipment due to drastic changes. Finally, the high temperature and high pressure sample is taken out for subsequent analysis.

[0067] The obtained cast and high temperature and high pressure alloy ingots are prepared into samples of certain specifications for testing and characterization.

[0068] The structure and performance of the cast and high temperature and high pressure alloys prepared by the above method are characterized as follows:

[0069] (5) Material phase characterization and mechanical properties testing:.

[0070] Figure 6 The Al 40 Mg 40 Li 10 Zn 10 The XRD spectrum of the as-cast sample material shows that its main phase is a variety of intermetallic compound phases, including Al 12 Mg 17 , Al3Mg2, MgZn2, and LiMgAl2. Figure 7 The Al 40 Mg 40 Li 10 Zn 10 Room temperature compressive stress-strain diagram of the as-cast sample material, from which it can be seen that its maximum compressive strength at room temperature is ~226MPa and the fracture strain is <1%; Figure 8 The Al 40 Mg 40 Li 10 Zn 10The XRD spectrum of the high temperature and high pressure sample material shows that its main phase is a face-centered cubic solid solution, and it also contains some intermetallic compound structures. It can be seen that after high temperature and high pressure treatment, the multiphase compound structure in the sample is transformed into a structure with a face-centered cubic solid solution phase as the matrix. Fig. 9 The Al 40 Mg 40 Li 10 Zn 10 The room temperature compressive stress-strain diagram of the high temperature and high pressure sample material shows that its room temperature compressive yield strength is 880 MPa and the fracture strain is ~2.5%. It can be seen that the strength and plasticity of the synthesized alloy with face-centered cubic solid solution as the matrix are greatly improved. Fig.10 The Al 40 Mg 40 Li 10 Zn 10 The SEM images of the organizational structure morphology of the cast and high-temperature and high-pressure sample materials clearly show the organizational morphology of the cast multiphase intermetallic compounds. After high-temperature and high-pressure treatment, a structure with a face-centered cubic solid solution (black phase) as the matrix and some compound phases (white phase) is formed.

[0071] Example 3

[0072] Al 70 Mg 17 The preparation process of Li5Zn5Y3 lightweight high entropy is as follows:

[0073] (1) Raw material preparation: Pure elements are used as raw materials. Y is added using AlY master alloy. The oxide layer and impurities of the metal elements are removed and ultrasonic cleaning is performed in ethanol or acetone. The Li element is kept in a glove box for a long time. When used, the surface oxide scale is removed with a blade in the glove box, and then the sample without oxide scale is cut out. After mixing the ingredients in the glove box, it is waited for smelting.

[0074] (2) Weighing: The mass of each element and the AlY master alloy is calculated according to the atomic ratio of each component, and the precise weighing and proportioning are performed using a precision electronic balance; this is used for smelting the alloy, and the Li element is operated in a glove box;

[0075] (3) Alloy smelting: The ingot is prepared using a high vacuum induction melting furnace. Pure metals and AlY master alloys are placed in a crucible in sequence and induction smelted in a high-purity argon environment. After the alloy is melted, it is poured into a mold to obtain a cast alloy ingot.

[0076] (4) High temperature and high pressure treatment: The obtained alloy ingot is subjected to a high temperature and high pressure treatment of 12GPa / 1200K using a two-stage large press. First, the alloy sample is assembled in the first and second stages. Next, the pressure is gradually increased to 12GPa, and then heated to 1200 K, and the pressure and heat are gradually increased until the set value is reached. After reaching the set pressure and temperature, the high temperature and high pressure state is maintained for 8 minutes to ensure that the sample undergoes the required phase change. After the experiment, the temperature is lowered to room temperature, and then the pressure is gradually reduced to normal pressure to avoid damage to the sample or equipment due to drastic changes. Finally, the high temperature and high pressure sample is taken out for subsequent analysis.

[0077] The obtained cast and high temperature and high pressure alloy ingots are prepared into samples of certain specifications for testing and characterization.

[0078] The structure and performance of the cast and high temperature and high pressure alloys prepared by the above method are characterized as follows:

[0079] (5) Material phase characterization and mechanical properties testing:.

[0080] The Al 70 Mg 17 The main phases of the Li5Zn5Y3 cast sample are face-centered cubic solid solution and various intermetallic compound phases. Its maximum compressive strength at room temperature is 451MPa and its fracture strain is 17%. 70 Mg 17 The Li5Zn5Y3 high temperature and high pressure sample material is mainly composed of a single-phase face-centered cubic solid solution phase, and its maximum compressive yield strength at room temperature is 813 MPa and its fracture strain is 33%. Example 4

[0081] Al 67 Mg 15 The preparation process of Li5Zn5Cu5Y3 lightweight high entropy is as follows:

[0082] (1) Raw material preparation: Pure elements are used as raw materials. Y is added using AlY master alloy. The oxide layer and impurities of the metal elements are removed and ultrasonic cleaning is performed in ethanol or acetone. The Li element is kept in a glove box for a long time. When used, the surface oxide scale is removed with a blade in the glove box, and then the sample without oxide scale is cut out. After mixing the ingredients in the glove box, it is waited for smelting.

[0083] (2) Weighing: The mass of each element and the AlY master alloy is calculated according to the atomic ratio of each component, and the precise weighing and proportioning are performed using a precision electronic balance; this is used for smelting the alloy, and the Li element is operated in a glove box;

[0084] (3) Alloy smelting: The ingot is prepared using a high vacuum induction melting furnace. Pure metals and AlY master alloys are placed in a crucible in sequence and induction smelted in a high-purity argon environment. After the alloy is melted, it is poured into a mold to obtain a cast alloy ingot.

[0085] (4) High temperature and high pressure treatment: The alloy ingot is subjected to a high temperature and high pressure treatment of 14 GPa / 1400 K using a two-stage large press. First, the alloy sample is assembled in the first and second stages. Next, the pressure is gradually increased to 14 GPa, and then heated to 1400 K, and the pressure and heat are gradually increased until the set value is reached. After reaching the set pressure and temperature, the high temperature and high pressure state is maintained for 10 minutes to ensure that the sample undergoes the required phase change. After the experiment, the temperature is lowered to room temperature, and then the pressure is gradually reduced to normal pressure to avoid damage to the sample or equipment due to drastic changes. Finally, the high temperature and high pressure sample is taken out for subsequent analysis.

[0086] The obtained cast and high temperature and high pressure alloy ingots are prepared into samples of certain specifications for testing and characterization.

[0087] The structure and performance of the cast and high temperature and high pressure alloys prepared by the above method are characterized as follows:

[0088] (5) Material phase characterization and mechanical properties testing:

[0089] The Al 67 Mg 15 The main phases of the Li5Zn5Cu5Y3 cast sample are face-centered cubic solid solution and various intermetallic compound phases. Its maximum compressive strength at room temperature is 472MPa and its fracture strain is 14%. 67 Mg 15 The Li5Zn5Cu5Y3 high temperature and high pressure sample material is mainly composed of a face-centered cubic solid solution phase, with a maximum compressive yield strength of 865MPa at room temperature and a fracture strain of 26%.

[0090] Summary of results of various embodiments

[0091] .

[0092] The above is a detailed introduction to a lightweight, high-strength, high-entropy Al alloy block material, preparation method and application provided in the embodiments of the present application. The description of the above embodiments is only used to help understand the method and core idea of ​​the present application; at the same time, for those of ordinary skill in the art, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

[0093] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different nouns to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. As mentioned throughout the specification and claims, "including" and "comprising" are open-ended terms, so they should be interpreted as "including / including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problem within a certain error range and basically achieve the technical effect. The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application, and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the attached claims.

[0094] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.

[0095] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0096] The above description shows and describes several preferred embodiments of the present application, but as mentioned above, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present application, and should be within the scope of protection of the claims attached to the present application.

Claims

1. A lightweight, high-strength, high-entropy Al alloy bulk material, characterized in that: The atomic percentage expression of the high entropy Al alloy bulk material is Al a Mg b Li c Zn d , the atomic percentage of each component is: 40≤a≤80at%, 15≤b≤50at%, 0<c≤20at%, 0<d≤20at%, and a+b+c+d=100at%; the lightweight, high-strength and high-entropy Al alloy block material has a face-centered cubic solid solution structure composed of multiple principal metal elements.

2. The high entropy Al alloy bulk material according to claim 1, characterized in that: The high entropy Al alloy bulk material also includes M e , M is at least one of Cu, Y, La or Ce, and 0≤e≤20at%.

3. The high entropy Al alloy bulk material according to claim 2, characterized in that: When M is Cu, a=70at%, b=15at%, c=5at%, d=5at%, e=5at%, the atomic percentage expression of the high entropy Al alloy bulk material is Al 70 Mg 15 Li5Zn5Cu5, density 2.7 g / cm 3 , at room temperature, the compressive strength is 770MPa and the compression plasticity is 31%.

4. The high entropy Al alloy bulk material according to claim 1, characterized in that: When a=40.0at%, b=40.0at%, c=10.0at%, d=10.0at%, the atomic percentage expression of the high entropy Al alloy bulk material is Al 40 Mg 40 Li 10 Zn 10 , density is 2.54 g / cm 3 , at room temperature, the compressive strength is 880MPa and the compression plasticity is 2.5%.

5. A method for preparing a high entropy Al alloy material according to any one of claims 1 to 4, characterized in that: The preparation method specifically comprises the following steps: S1) Weigh each raw material according to the designed ratio, the purity of the raw material exceeds 99.9%, remove the surface oxide layer, and put it into ethanol or acetone for ultrasonic cleaning; S2) melting the raw materials processed in S1) in a vacuum induction melting furnace to obtain alloy ingots; S3) Using a two-stage large press, the alloy ingot obtained in S2) is subjected to high temperature and high pressure treatment to obtain a lightweight, high-strength, high-entropy Al alloy block material with a face-centered cubic solid solution phase.

6. The preparation method according to claim 5, characterized in that: The specific process parameters in S2) are: the smelting atmosphere is high-purity argon; the smelting temperature is 700-900°C.

7. The preparation method according to claim 5, characterized in that: The high pressure range in S3) is 10-15 GPa, the high temperature range is 1000-1500 K, and the insulation time is 5-10 min.

8. The preparation method according to claim 5, characterized in that: The density of the lightweight, high-strength, high-entropy Al alloy block material prepared by the preparation method is 2.4-2.86 g / cm 3 , strength is 600-980MPa, and plasticity is 2.5%-35%.

9. A lightweight, high-strength, high-entropy Al alloy block material as described in any one of claims 1 to 4 is used in the preparation of parts and structural parts of aviation transportation equipment.

Citation Information

Patent Citations

  • Aluminum-lithium-magnesium-based lightweight high-entropy alloy and preparation method thereof

    CN114107751A